One‐Pot Synthesis of Unsaturated Polyester Bioelastomer with Controllable Material Curing for Microscale Designs. Issue 16 (17th July 2019) - Davenport Huyer, Locke; Bannerman, A. Dawn; Wang, Yufeng; Savoji, Houman; Knee‐Walden, Ericka J.; Brissenden, Amanda; Yee, Bess; Shoaib, Mohammad; Bobicki, Erin; Amsden, Brian G.; Radisic, Milica
Abstract: Synthetic polyester elastomeric constructs have become increasingly important for a range of healthcare applications, due to tunable soft elastic properties that mimic those of human tissues. A number of these constructs require intricate mechanical design to achieve a tunable material with controllable curing. Here, the synthesis and characterization of poly(itaconate‐ co‐ citrate‐ co‐ octanediol) (PICO) is presented, which exhibits tunable formation of elastomeric networks through radical crosslinking of itaconate in the polymer backbone of viscous polyester gels. Through variation of reaction times and monomer molar composition, materials with modulation of a wide range of elasticity (36–1476 kPa) are generated, indicating the tunability of materials to specific elastomeric constructs. This correlated with measured rapid and controllable gelation times. As a proof of principle, scaffold support for cardiac tissue patches is developed, which presents visible tissue organization and viability with appropriate elastomeric support from PICO materials. These formulations present potential application in a range of healthcare applications with requirement for elastomeric support with controllable, rapid gelation under mild conditions. Abstract : A family of photocrosslinkable, elastic, and degradable polyester materials is developed with highly tunable soft biomaterial properties. These poly(itaconate‐ co ‐citrate‐ co ‐octanediol) (PICO) materials are synthesized in a two‐step polymerization reaction followed by rapid crosslinking, yielding controllable properties. PICO has application in cellular microenvironments, including engineered cardiac tissue, that require elastic mechanical support.